Effects of counterion size and backbone rigidity on the dynamics of ionic polymer melts and glasses12. Issue 40 (4th October 2017) - Fu, Yao; Bocharova, Vera; Ma, Mengze; Sokolov, Alexei P.; Sumpter, Bobby G.; Kumar, Rajeev
Abstract : Backbone rigidity, counterion size and the static dielectric constant affect the glass transition temperature, segmental relaxation time and decoupling between counterion and segmental dynamics in significant manners. Abstract : It is well-known that the nature and size of the counterions affect the ionic conductivity and glass transition temperature of ionic polymers in a significant manner. However, the microscopic origin of the underlying changes in the dynamics of chains and counterions is far from completely understood. Using coarse-grained molecular dynamics simulations of flexible and semi-flexible ionic polymers, we demonstrate that the glass transition temperature of ionic polymeric melts depends on the size of monovalent counterions in a non-monotonic manner. The glass transition temperature is found to be the highest for the smallest counterions and decreases with an increase in the counterion radii up to a point, after which the glass transition temperature increases with a further increase in the radii. This behavior is because the counterions have significant effects on the coupled dynamics of the charges on the chains and counterions. In particular, increase in the radii of the counterions leads to strongly coupled dynamics between the charges on the chains and the counterions. The static dielectric constant of the polymer melts also has a significant effect on the coupling and the glass transition temperature. The glass transition temperature is predicted to decrease with an increase in the dielectric constant. This, in turn, leads to an increase in the diffusion constant of the counterions at a given temperature. Backbone rigidity is shown to increase the glass transition temperature and decrease the coupling. Furthermore, faster counterion dynamics is predicted for the melts of semi-flexible chains in comparison with flexible chains at the same segmental relaxation time. As the semi-flexible chains tend to have a longer segmental relaxation time, semi-flexible polymers with high dielectric constants are predicted to have diffusion constants of counterions comparable with flexible polymers.